Apoptosis induction of poly-S-nitrosated human serum albumin in resistant solid tumor under hypoxia can be restored by phosphodiesterase 5 inhibition - Ikeda, M.; Ishima, Y.; Chuang, Victor; Ikeda, T.; Kinoshita, R.; Watanabe, H.; Ishida, T.; Otagiri, M.; Maruyama, T. (Elsevier Inc, 2016)
Poly-S-nitrosated human serum albumin (Poly-SNO-HSA) delivered and accumulated nitric oxide (NO) in tumors and induces apoptosis. Tumor hypoxia is strongly associated with malignant progression and tumor resistance to therapy. In this study, we examined the cytotoxic effect of Poly-SNO-HSA under hypoxia on the murine colon 26 adenocarcinoma (C26) cells in vitro and in vivo. Under hypoxia, at about 4 times LD50 dose of Poly-SNO-HSA in vitro, the reactive oxygen species production was hindered but apoptotic cells were induced via cGMP pathway as the effect was suppressed by a soluble guanylate cyclase inhibitor, NS2028. The apoptosis induction effect of low dose Poly-SNO-HSA on C26 cells in vitro under hypoxia can be restored by a phosphodiesterase 5 (PDE5) inhibitor, vardenafil. In C26-bearing mice, Poly-SNO-HSA/vardenafil combination treatment significantly suppressed the tumor volume compared with Poly-SNO-HSA or vardenafil treatment alone. Furthermore, the core tumor tissues showed increased expression of caspase-3 than the non-core tissue. The expression of caspase-3 appeared to overlap with the hypoxic zone of tumor tissues. Similar results were also obtained when the experiments were repeated using Epimedium extract, a natural herbal supplement with PDE5 inhibition activity. In conclusion, Poly-SNO-HSA/PDE5 inhibitors combination therapy is a promising approach for enhancing the anticancer therapeutic effects of Poly-SNO-HSA against not only anti-cancer drug resistance but also hypoxic stress related solid tumor resistance.